UK public sector weak on security. (August 2015) - Unknown
Abstract : New research by security firm Sophos into the state of IT security in the UK's public sector found that nearly half of workers in local government and police forces were doubtful of their organisations' ability to defend against today's cyber-threats. And most of the rest had no idea.